An Analysis of Early Childhood Creativity Development Through Eggshell Media - Putri Lestari, Larasati Wisnu; Fitria, Evy; Rohmawati, Diana; Putri, Ratu Rahmawati; Maisah, Siti; Suarah, Suarah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Providing stimulation according to the stages of development in early childhood is an effective approach to enhancing various aspects of growth, including creativity. Creativity can be nurtured through activities designed by teachers, such as collage-making and painting using eggshells. This study aims to analyze creativity in early childhood through collage and painting activities using eggshells at TK Islam Bani Usman Manunggal. This research employs a descriptive qualitative approach, which researchers provide observation for eight students in the class, interview one teacher to get her perspective and documentation to obtained the data. The result shows that the creativity of students appear when they explored themselves in activities using eggshells and also painting it. Therefore, the researcher hopes that the findings of this study can assist teachers in fostering creativity and fine motor skills in early childhood through painting and collage activities using eggshells.